RANCANG BANGUN BOX PENDINGIN IKAN BERBASIS PANEL SURYA DENGAN MENGGUNAKAN ELEMEN PENDINGIN PALTIER UNTUK KAPAL NELAYAN PESISIR - Fernando Saputra; Hidayatullah, Muhammad; Aulia, Masyitah; Jaya , Ahmad (Program Studi Teknik Elektro, 2024)
From 2019 to 2020 there has been a decrease in fish catches. This is due to several causative factors, one of which is decay. Previously, some fishermen had to prepare many things to overcome decay even with preservation methods, most of which still use conventional methods in the form of using ice cubes. However, such methods are still lacking in terms of maintaining the quality of fish. Some have switched to using Cold Storage machines, but not all fishermen can afford to have them. So this is what made researchers conduct this study entitled